Nomina instrumenti blandt komposita i dansk og deres polske ækvivalenter - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2015)
The article is an attempt at analyzing Danish nomina instrumenti among compounds and finding patterns of equivalence in Polish. The analysis of the collected corpus has shown that the Polish equivalents of the Danish compounds are not compounds but, with the exception of a minor group of derivates, they have the form of phrases. The analysis has shown patterns of regular Polish structures corresponding to the Danish compounds.